Tissue-specific disallowance of housekeeping genes: The other face of cell differentiation - Thorrez, Lieven; Laudadio, Ilaria; Van Deun, Katrijn; Quintens, Roel; Hendrickx, Nico; Granvik, Mikaela; Lemaire, Katleen; Schraenen, Anica; Van Lommel, Leentje; Lehnert, Stefan; Aguayo-Mazzucato, Cristina; Cheng-Xue, Rui; et al. (Genome Research, 2011)
We report on a hitherto poorly characterized class of genes that are expressed in all tissues, except in one. Often, these genes have been classified as housekeeping genes, based on their nearly ubiquitous expression. However, the specific repression in one tissue defines a special class of “disallowed genes.” In this paper, we used the intersection-union test to screen for such genes in a multi-tissue panel of genome-wide mRNA expression data. We propose that disallowed genes need to be repressed in the specific target tissue to ensure correct tissue function. We provide mechanistic data of repression with two metabolic examples, exercise-induced inappropriate insulin release and interference with ketogenesis in liver. Developmentally, this repression is established during tissue maturation in the early postnatal period involving epigenetic changes in histone methylation. In addition, tissue-specific expression of microRNAs can further diminish these repressed mRNAs. Together, we provide a systematic analysis of tissue-specific repression of housekeeping genes, a phenomenon that has not been studied so far on a genome-wide basis and, when perturbed, can lead to human disease.
10.1101/gr.109173.110